(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Early diagnosis of acute kidney injury is critical for decision-making. Neutrophil gelatinase-associated lipocalin (NGAL) is a biomarker introduced for early detection of acute kidney injury (AKI). We evaluated urinary NGAL level in hospitalized patients due to poisoning as a predictor of AKI. Methods. We studied patients with poisoning due to various causes. Urinary NGAL and urine creatinine levels were measured. Serum creatinine levels were measured for all patients at baseline and after 24 and 48 hours. Then, a ROC curve developed for urinary NGAL, and cutoff point and accuracy of urinary NGAL test were determined. Results. Ninety hospitalized patients with acute poisoning were consecutively recruited into the study over an eight-months period. With the gold standard test (i.e., serum creatinine measurement), 21 patients were diagnosed with acute kidney injury (AKI) and 69 with non-AKI, whereas according to ROC curve, at a cutoff point of 110 ng/ml, urinary NGAL with an 81% sensitivity and 91.3% specificity distinguished 23 patients with AKI and 67 with non- AKI. The false positive and false negative values of urinary NGAL test were 8.7% and 19%, respectively. The positive predictive value and negative predictive value of urinary NGAL were estimated to be 73.9% and 94%, respectively. Conclusion. Urinary NGAL test, with an AUC of ROC curve of approximately 90% and a sensitivity of 81%, can be used for early detection of AKI. It has a high specificity (91.3%), indicating that the percentage of false positive cases (8.7%) will be small.